Ղունկիանոս Կարնեցու «Գովասանք գրքույս» բանաստեղծությունը - Արիադնա Հարությունյան (ՀՀ ԳԱԱ հրատ.)
Панегирик, начинающийся словами «Хвала написанному мной»–образец армянской лирики, автором которого является поэт Лункианос Карнеци, oдин из последних представителей армянской поэзии конца XVIII – начала XIX вв. Общая теоретическая оценка стихотворения позволяет выделить типологические черты, присущие армянской поэзии этого времени и то, как они отразились в панегирике. Своими песнями автор предоставляет богатый материал для дальнейшего исследования его самобытного творчества. The panegyric, which begins with the words “Praise to my book”, is a piece of Armenian lyrics written by the poet Ghunkianos Karnetsi, one of the last representatives of the Armenian poetry of the end of the 18th and the beginning of the 19th century. General theoretical assessment of the poem allows to distinguish the typological features proper to the Armenian poetry of that period and, how they are reflected in the panegyric. With his songs the author provides rich material for the further investigation of his distinctive creative life.
Keywords: Literature; Language and Literature